(untitled) (The Voz a Vos Bulletin, 2021)
The development of didactics linked to acts of creation and the work of sensitive exploration in the body and thought from the collective seeks to enhance the creative processes of the members of the Backú Artistic Collective, to generate a montage of research-creation that speaks of the ruana as a symbol of the prevalence of the Cundiboyacense peasant. Starting from creation laboratories that put into practice the method of collective creation proposed by Enrique Buenaventura and Santiago García.